Interpolation of functionals by integral continued C-fractions - Makarov, V.L.; Pahirya , M.M. (Reports of the National Academy of Sciences of Ukraine, 2018)
The problem of interpolation of a functional by an integral continued C-fraction if its value is known on the set of continual nodes is studied. The necessary and sufficient conditions for its solvability are found. In the partial case, such an integral continued fraction contains an interpolation continued C-fraction, which is used to approximate the functions of one variable.